2019
DOI: 10.1177/0284185119867644
|View full text |Cite
|
Sign up to set email alerts
|

Altered effective connectivity of primary visual cortex in primary angle closure glaucoma using Granger causality analysis

Abstract: Background Previous neuroimaging studies demonstrated that primary angle closure glaucoma patients were associated with abnormal intrinsic brain activity in primary visual cortex (V1). Purpose The purpose of this study was to investigate the effective connectivity patterns of V1 in patients with primary angle closure glaucoma. Material and Methods Thirty-seven patients with primary angle closure glaucoma (20 men, 17 women) and 36 healthy controls (20 men, 16 women) closely matched for age, sex, and education, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Meanwhile, Jiang et al (2020) reported that patients with PACG showed abnormal effective connectivity between V1 and the higher visual area, motor cortices, somatosensory cortices, and frontal lobe. Graham et al (2021) found that dogs with unilateral PACG showed reduced fractional anisotropy (FA) in the visual pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Jiang et al (2020) reported that patients with PACG showed abnormal effective connectivity between V1 and the higher visual area, motor cortices, somatosensory cortices, and frontal lobe. Graham et al (2021) found that dogs with unilateral PACG showed reduced fractional anisotropy (FA) in the visual pathway.…”
Section: Introductionmentioning
confidence: 99%